Effectiveness of Educational Program on Nurses Knowledge Toward Rehabilitation for Patients with Cardiac Heart Attack - Hakema S. Hassan; Ahmed A. Alawee Naseer (Kufa Journal for Nursing Sciences)
Objective: The study aims to evaluate the effectiveness of nursing education program on the nurses knowledge toward cardiac rehabilitation phase one for patients with heart attack